In silico gene expression analysis reveals glycolysis and acetate anaplerosis in IDH1 wild-type glioma and lactate and glutamate anaplerosis in IDH1-mutated glioma - Khurshed, Mohammed (Oncotarget, 2017)
Hotspot mutations in isocitrate dehydrogenase 1 (IDH1) initiate low-grade glioma and secondary glioblastoma and induce a neomorphic activity that converts α-ketoglutarate (α-KG) to the oncometabolite D-2-hydroxyglutarate (D-2-HG). It causes metabolic rewiring that is not fully understood. We investigated the effects of IDH1 mutations (IDH1(MUT)) on expression of genes that encode for metabolic enzymes by data mining The Cancer Genome Atlas. We analyzed 112 IDH1 wild-type (IDH1(WT)) versus 399 IDH1(MUT) low-grade glioma and 157 IDH1(WT) versus 9 IDH1(MUT) glioblastoma samples. In both glioma types, IDH1(WT) was associated with high expression levels of genes encoding enzymes that are involved in glycolysis and acetate anaplerosis, whereas IDH1(MUT) glioma overexpress genes encoding enzymes that are involved in the oxidative tricarboxylic acid (TCA) cycle. In vitro, we observed that IDH1(MUT) cancer cells have a higher basal respiration compared to IDH1(WT) cancer cells and inhibition of the IDH1(MUT) shifts the metabolism by decreasing oxygen consumption and increasing glycolysis. Our findings indicate that IDH1(WT) glioma have a typical Warburg phenotype whereas in IDH1(MUT) glioma the TCA cycle, rather than glycolytic lactate production, is the predominant metabolic pathway. Our data further suggest that the TCA in IDH1(MUT) glioma is driven by lactate and glutamate anaplerosis to facilitate production of α-KG, and ultimately D-2-HG. This metabolic rewiring may be a basis for novel therapies for IDH1(MUT) and IDH1(WT) glioma.